Services Marketing - Clow Kenneth E; Kurtz David L (John Wiley & Sons, Ltd, 1998)
This practical guide takes a behavioral and managerial approach to one of the fastest-growing fields in marketing: services marketing. About the Authors, Preface, The Foundation of Services Marketing, The Purchase Process for Services, Service Quality, Managing the Service Outcome, Operations, People, Environment, Pricing, Distribution, Service Strategies, Customer Retention, Jefferson-Pilot Corporation, Index.